2004
DOI: 10.1007/s11167-005-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Gold from ores and concentrates by leaching with the use of cyanides and alternative reagents

Abstract: The problems associated with gold mining are considered from the standpoint of application of heap leaching, a method for gold recovery. Data on the kinetics and mechanism of gold dissolution in cyanide and alternative solvents [thiocarbamide solutions containing Fe(III) ions and hypochlorite-chloride bromine-bromide, iodine-iodide, and copper-thiosulfate solutions], which make it possible not only to improve the working efficiency in gold mining, but also to lessen the contamination of the environment with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…Significant occupational exposure to mercury occurs since 28% of the mercury used is precipitated on the zinc shavings and is lost to the atmosphere when the shavings are burned. Methods of extraction that are safer to health and the environment, and are economically competitive, include ammonium thiosulfate [30], thiocarbamide hypochlorite and halogen-halide solutions [31].…”
Section: Artisanal and Small-scale Miningmentioning
confidence: 99%
“…Significant occupational exposure to mercury occurs since 28% of the mercury used is precipitated on the zinc shavings and is lost to the atmosphere when the shavings are burned. Methods of extraction that are safer to health and the environment, and are economically competitive, include ammonium thiosulfate [30], thiocarbamide hypochlorite and halogen-halide solutions [31].…”
Section: Artisanal and Small-scale Miningmentioning
confidence: 99%
“…염소-차아염소산은 시안의 24시간보다, 그리고 티 오요소의 15분보다 gold를 매우 빠르게 용해시키 고, 또한 독성이 상대적으로 적기 때문에 시안의 대체 용매제로 사용된다 (Kozin and Melekhin, 2004;Hilson and Monhemius, 2006). 그러나 차아염소산 나트륨은 염산이나 황산과 반응하여 염소를 생성 시키며, 이때 생성된 염소 가스는 독성이 있으므로 접촉을 피해야 한다 (Hilson and Monhemius, 2006).…”
Section: 서 론unclassified
“…This indicated that such a formulation may have the potential to treat aqueous streams typically produced during leaching of gold from ore minerals. 14 In a subsequent paper, 15 the authors showed that the adsorption equilibrium of gold on the membrane at room temperature followed a Langmuir-type relationship:…”
Section: Introductionmentioning
confidence: 99%